Descemet's stripping automated endothelial keratoplasty with anterior chamber intraocular lenses - Tan, Donald; Htoon, Hla M; Ang, Marcus (British journal of ophthalmology, 2014)
[...]completely excluding subjects with less than 3 years of follow-up as suggested by Mittal and Garg would actually lead to a selection bias, missing 14 (out of a possible total 19) graft failures and further strengthening our study conclusions-although in an inaccurate way.